Fair Trade: The Legacy of Osler and Penfield for Neuroscience and Ethics - Fins, Joseph (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
In this essay I explore the cross-border contributions of William Osler and Wilder Penfield to neuroscience and ethics and make the argument for continued collaboration between Canada and the United States.